Subducted and Melanotic Cells in Advanced Age-Related Macular Degeneration Are Derived From Retinal Pigment Epithelium - Zanzottera, Emma C. (Invest Ophthalmol Vis Sci, 2015)
PURPOSE. To describe, illustrate, and account for two cell types plausibly derived from RPE in geographic atrophy (GA) and choroidal neovascularization (CNV) of AMD, using melanosomes, lipofuscin, and basal laminar deposit (BLamD) as anatomical markers. METHODS. Human donor eyes with GA (n = 13) or CNV (n = 39) were histologically processed, photodocumented, and analyzed for frequencies of occurrence. We defined RPE as cells containing spindle-shaped melanosomes and RPE lipofuscin, internal to basal lamina or BLamD, if present, or Bruch's membrane if not, and RPE-derived cells as those plausibly derived from RPE and not attached to basal lamina or BLamD. RESULTS. ‘Subducted’ cells contain RPE melanosomes and localize to the sub-RPE space, on Bruch's membrane. Credible transitional forms from RPE cells were seen. Grades of RPE overlying ‘Subducted’ cells were ‘Atrophic with BLamD’ (32.2% vs. 37.0% of ‘Subducted,’ for GA and CNV eyes, respectively), ‘Dissociated’ (22.0% vs. 21.7%), ‘Nonuniform’ (22.0% vs. 23.9%), and ‘Sloughed’ RPE (10.2% vs. 4.3%). Found exclusively in CNV scars, ‘Melanotic’ cells containing spherical melanosomes were adjacent to ‘Entombed’ RPE with spindle-shaped and spherical melanosomes. Of subretinal ‘Melanotic’ cells, 40.0% associated with ‘Atrophy with BLamD,’ 36.8% with ‘Atrophy without BLamD,’ and 20.6% with ‘Entombed.’ CONCLUSIONS. ‘Dissociated’ RPE within atrophic areas may be the source of ‘Subducted’ cells. ‘Entombed’ RPE within fibrovascular and fibrocellular scars may be the source of ‘Melanotic’ cells. An imaging correlate for ‘Subducted’ cells awaits discovery; ‘Melanotic’ cells appear gray-black in the CNV fundus. Results provide a basis for future molecular phenotyping studies.